Genetic associations of growth and lactation curve components in polled Hereford cattle - J.B. Jr. Glaze; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1999)
Weight and milk production records of Polled Hereford cows born from 1967 to 1979 were used to fit growth and lactation curves. A multiple-trait, derivative-free, restricted maximum likelihood (MTDFREML) procedure, utilizing a full animal model, was used to estimate variances and covariances for the components of the growth and lactation curves. For the growth curve, W=A+B(1-e-kt) components A, B, and k each had moderate to high heritabilities ranging from .35 to .72. The genetic correlation between growth curve components A and B was positive (.42), whereas the genetic correlations between A and K (-.34) and between B and K (-.74) were negative. In the lactation curve, Yn=n/(aekm) heritabilities of components k and a were .15 and .40, respectively. The genetic correlation between these lactation curve components was -.78.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Growth curve; Lactation curve; Heritability; Genetic correlation; Polled Hereford